Maturation and germination of somatic embryos of guava var. Cuban Red Dwarf EEA-1840 - Vilchez-Perozo, Jorge; Albany , Nilca; Pliego , Fernando; Sánchez , Carolina (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
Somatic embryogenesis is an alternative for the accelerated propagation of promising guava (Psidium guajava L.) materials of agronomic interest. However, low maturation and germination rates of somatic embryos are some of the aspects that limit its application in breeding programs for different purposes. In this sense, the effect of three concentrations (0, 1 and 1.5 mg.L-1) of abscisic acid (ABA) on embryo maturation and two concentrations of sucrose (3 and 5 %) and Murashige and Skoog (MS) macronutrients (50 and 100 %) on the germination of somatic embryos of guava var. Cuban Red Dwarf EEA-1840 were studied. After six weeks of culture, ABA had a negative effect on somatic embryo maturation in culture media supplemented with 1 or 1.5 mg.L-1, whereas 3.95 to 5.49 times more mature embryos were observed in the absence of ABA. Germination of somatic embryos was significantly improved when the concentration of macronutrient in the culture medium was reduced independently of the sucrose concentration [MS 50 % + 3 % of sucrose (73,3 %) and MS 50 % + 5 % de sucrose (55,0 %)]. It is concluded that the simplification of the culture media with reduction of the macroelements MS and sucrose to standard concentration favors the germination of mature embryos of guava var. Cuban Red Dwarf EEA-1840.